2017
DOI: 10.15406/apar.2017.06.00238
|View full text |Cite
|
Sign up to set email alerts
|

Breeding for Quality Improvement in Turmeric (Curcuma longa L.): a Review

Abstract: Turmeric (Curcuma longa L.) is an economically important spice and medicinal plant for production of curcuminoids, oleoresin, essential oil which are used in pharmaceutical and cosmetics industries. Presence of these contents in turmeric determine its quality. Average productivity and quality of turmeric is not satisfactory because of the poor genetic materials and non-availability of quality materials. Conventional clonal selection takes long time and slow progress to achieve the same level of quality improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Generally, the lowest curcumin contents were obtained from HT3/2002 variety regardless of the drying and curing method used. This discrepancy in curcumin retention between turmeric varieties with similar postharvest operations may be due to genetic factors indicating that phytochemicals are attributes of biosynthetic gene expression pathways [28]. Several studies have already reported the presence of variations in curcumin content among different turmeric varieties.…”
Section: Curcuminmentioning
confidence: 99%
“…Generally, the lowest curcumin contents were obtained from HT3/2002 variety regardless of the drying and curing method used. This discrepancy in curcumin retention between turmeric varieties with similar postharvest operations may be due to genetic factors indicating that phytochemicals are attributes of biosynthetic gene expression pathways [28]. Several studies have already reported the presence of variations in curcumin content among different turmeric varieties.…”
Section: Curcuminmentioning
confidence: 99%
“…11,15 In addition, DNA markers have provided a competent device to facilitate the preservation and managing of plant genetic resources. 16,17 Importantly, the polymorphic information content (PIC) value has been extensively used as a discriminatory power tool and has highly succeeded in accumulating the accurate knowledge of turmeric genetic variability over the last few years in many diversity studies such as refs 4, 11, 18, and 19. With this background, the present study particularly aimed to determine the genetic variation/variability among certain turmeric genotypes using SSR DNA-based molecular markers to identify elite genotypes as well as effective SSR markers for further utilization in genetic development programs of turmeric germplasm for high-yielding cultivars with desirable traits.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, polymerase chain reaction (PCR)-based marker systems have become available with the development of molecular markers and their many perceived advantages; it is crucial that these techniques are applied to assess genetic diversity in genotype collections to supplement and refine the morphologically based classification. DNA-based molecular markers, viz., intersimple sequence repeats, simple sequence repeats (SSRs), and random amplified polymorphic DNA are commonly used for molecular studies in turmeric to explore the genetic diversity of different collections of turmeric germplasm for further utilization in various breeding schemes including classical as well as marker-assisted selection to develop better and desirable turmeric genotypes/cultivars. , In this regard, grouping of turmeric genotypes based on geographic onset by polymorphic SSR markers would be very useful for genetic research studies. , In addition, DNA markers have provided a competent device to facilitate the preservation and managing of plant genetic resources. , Importantly, the polymorphic information content (PIC) value has been extensively used as a discriminatory power tool and has highly succeeded in accumulating the accurate knowledge of turmeric genetic variability over the last few years in many diversity studies such as refs , , , and .…”
Section: Introductionmentioning
confidence: 99%
“…Turmeric (Curcuma longa L.) is a member of the gingerbread plant family (Zingiberaceae family), frequently appears in yellow color and is exploited as a food additive, spice and color agent [5][6][7]. It has also been incorporated into traditional medicines such as Ayurveda, Siddha, and Unani [8].…”
Section: Introductionmentioning
confidence: 99%